2005
DOI: 10.1002/ange.200500645
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Mikroarrays als Decodierungswerkzeuge in der kombinatorischen Chemie und der chemischen Biologie

Abstract: Entschlüsselungstechnik: DNA‐Mikroarrays werden außer in der Transkriptionsanalyse zurzeit vermehrt auch zur Decodierung kombinatorischer Bibliotheken eingesetzt. Zu aktuellen Anwendungsbeispielen zählen das Auffinden neuer organischer Reaktionen und das Screening von Peptidnucleinsäure‐codierten Inhibitorbibliotheken zur Untersuchung neuer proteolytischer Aktivitäten im Extrakt der Hausstaubmilbe (siehe Bild).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
4
0
4
Order By: Relevance
“…[275] A further case in point is the combination of multiple orthogonal DNA assembly processes with the stable biotin/ SAv template, which avoids laborious DNA labeling of proteins. [243,255,[276][277][278][279] In several studies, reviewed elsewhere, [16,280,281] Niemeyer and co-workers employed the complexation of biotinylated proteins with SAv-DNA to form protein-oligonucleotide preconjugates (Figure 11). These preconjugates were then immobilized onto a surface displaying complementary oligonucleotides.…”
Section: Dna-modified Surfacesmentioning
confidence: 99%
“…[275] A further case in point is the combination of multiple orthogonal DNA assembly processes with the stable biotin/ SAv template, which avoids laborious DNA labeling of proteins. [243,255,[276][277][278][279] In several studies, reviewed elsewhere, [16,280,281] Niemeyer and co-workers employed the complexation of biotinylated proteins with SAv-DNA to form protein-oligonucleotide preconjugates (Figure 11). These preconjugates were then immobilized onto a surface displaying complementary oligonucleotides.…”
Section: Dna-modified Surfacesmentioning
confidence: 99%
“…[24] Recent applications of the DDI principle have demonstrated that DNA microarrays can be used efficiently as decoding tools in combinatorial chemistry and chemical biology. [25] In addition to this field of research, the heterogeneous hybridization implemented in DDI is also important for DNA computing on surfaces (see Section 6.1). The hybridization of short complementary DNA oligonucleotides can also be utilized for the assembly of metal and semiconductor nanoparticles tagged with appropriate DNA oligomers.…”
Section: General Considerations Of Dna-sequence Designmentioning
confidence: 99%
“…In the early 1980s, Seeman conducted pioneering work on the construction of artificial nucleic acid architectures using synthetic DNA branched junction motifs mainly containing three and four arms (motifs 1 and 2 in Figure 4), [37] which are schematic representation of DNA-based directional assembly of four different nanoscale building blocks to form a stoichiometrically and spatially defined supramolecular aggregate. [28] The upper section was reprinted with permission from reference [25].…”
Section: Junctions and Latticesmentioning
confidence: 99%
“…5, 6 Motivated by the extraordinary performance of the DNA‐directed immobilization (DDI) of proteins and other molecular and colloidal components,7 we herein describe that micropatterns of cell‐surface ligands can be generated on DNA microarrays by the DDI method and that the resulting surfaces are suitable substrates for the growth of fibroblast cells (Figure 1). This approach should have significant advantages over conventional spotting procedures because it would enable the implementation of the power of DNA microarrays as decoding tools in combinatorial synthesis and screening of ligands8 into cellular biology research. To experimentally investigate this hypothesis, we chose the well‐studied recognition of RGD peptide ligands by integrin surface receptors of fibroblast cells as the model system 911…”
mentioning
confidence: 99%